When brothers dwell together : the preeminence of younger siblings in the Hebrew Bible - Greenspahn, Frederick E., 1946- (Oxford University Press, 1994)
Although primogeniture is commonly assumed to have prevailed throughout the world and firstborns are regarded as most likely to achieve success, many of the most prominent figures in biblical literature are younger offspring, including Isaac, Jacob, Joseph, Moses, Samuel, David, and Solomon. Adducing evidence from a wide range of disciplines, this study demonstrates that ancient Israelite fathers were free to choose their primary heirs. Rather than being either legally mandated or a protest against the prevailing norm, the Bible's propensity for younger offspring conforms to a widespread folk motif, evoking innocence, vulnerability, and destiny. Within the biblical context, this theme heightens God's role in supporting ostensibly unlikely heroes. Drawing on the resources of law, anthropology, folklore, and linguistics, Greenspahn shows how these tales serve as complex parables of the relationship of God to his chosen people, also reflecting Israel's own discomfort and confusion about the contradiction between its theology of election and the reality of political weakness.